Meta-Accuracy of Very First Impressions: A Mini Review - Tsankova, Elena; Tair, Ergyul (Frontiers in Psychology, 2021)
The meta-accuracy of first impressions (i.e., how accurately one understands others’ perception of oneself) can be conceptualized and measured in various ways. In order to reduce conceptual and methodological overwhelm, facilitate understanding of the topic, and stimulate future work in the field, we conducted a brief introductory literature review on the meta-accuracy of first impressions. Following a definitions-and-methodology-focused overview of the historical development of the topic, we present comparative synthesis and analysis of the key conceptualization and measurement methods used to study the meta-accuracy of first impressions. We also summarize the central research themes and types of stimuli that have been studied in relation to the meta-accuracy of first impressions. Finally, we make several suggestions for further research that could be beneficial to the future development and expansion of the field.